Impact of Background Interference on Signal-To-Noise Ratio in Heat-Assisted Magnetic Recording - Kaitwanidvilai, Somyot; Chaiduangsri, Nuttapon; Tongsomporn, Damrongsak (My University, 2018)
We discuss background interference (BGI) arising from the read-back of preexisting data and adjacent tracks on a recording medium. A signal-To-noise ratio analysis is used to measure the impact of BGI in heat-Assisted magnetic recording in a spin-stand tester. The signal-To-noise ratio for a data track with an alternating field background was compared to a data track written over a pair of background tracks. We considered the effect of background track offsets: The distance between the background and data tracks. BGI, which depends on the background track offset, can degrade read-back performance. The dibit extraction technique is able to separate the linear dibit response and the BGI in the read-back waveform.
Keywords: background interference; dibit extraction; heat-Assisted magnetic recording; Information storage; side-reading effect; spin-stand recording tester